2014
DOI: 10.1063/1.4897144
|View full text |Cite
|
Sign up to set email alerts
|

Engineering 180° ferroelectric domains in epitaxial PbTiO3 thin films by varying the thickness of the underlying (La,Sr)MnO3 layer

Abstract: Role of dual-laser ablation in controlling the Pb depletion in epitaxial growth of Pb(Zr0.52Ti0.48)O3 thin films with enhanced surface quality and ferroelectric properties Effect of oxygen stoichiometry on the ferroelectric property of epitaxial all-oxide La 0.7 Sr 0.3 MnO 3 /Pb(Zr 0.52 Ti 0.48 )O 3 /La 0.7 Sr 0.3 MnO 3 thin-film capacitors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Obviously, the intensity of interfacial Al−O columns is higher than that of other Al−O columns, implying that the interface diffusion may occur between Al and Ni/Mn. The out-of-plane lattice parameters in the interface area have been investigated by geometrical lattice mapping directly on the high-resolution HAADF image using a 2D Gaussian fitting approach 50,51 . Figure 3c displays a plot of the out-of-plane lattice spacing against the distance, which provides evidence for the difference in the out-of-plane lattice parameters between LNMO and LAO across the interface.
Figure 3( a ) Atomic-resolution HAADF image of the LNMO/LAO interface, viewed along the [010] p LAO zone axis.
…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, the intensity of interfacial Al−O columns is higher than that of other Al−O columns, implying that the interface diffusion may occur between Al and Ni/Mn. The out-of-plane lattice parameters in the interface area have been investigated by geometrical lattice mapping directly on the high-resolution HAADF image using a 2D Gaussian fitting approach 50,51 . Figure 3c displays a plot of the out-of-plane lattice spacing against the distance, which provides evidence for the difference in the out-of-plane lattice parameters between LNMO and LAO across the interface.
Figure 3( a ) Atomic-resolution HAADF image of the LNMO/LAO interface, viewed along the [010] p LAO zone axis.
…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structural quality and growth behavior of the films can be understood with the knowledge of atomic details of the interface structure between the films and the substrates. Jin et al reported that the La 0.3 Sr 0.7 MnO 3 (LSMO) hillocks on Nb doped SrTiO 3 (STO) substrates could induce regular 180° domains in subsequently deposited PTO films 14,20 . A close investigation showed that interdiffusion across the LSMO/Nb‐STO interface leads to distinct structural and physical properties in the PTO/LSMO/Nb‐STO system.…”
Section: Introductionmentioning
confidence: 99%
“…The atomically controlled interface in epitaxial heterostructures, such as multilayers, 8 superlattices, [9][10][11] and ultrathin films, 12,13 play a prominent role in determining the microstructure evolution [14][15][16][17] and functionalities of the films. [18][19][20][21] The crystal structural quality and growth behavior of the films can be understood with the knowledge of atomic details of the interface structure between the films and the substrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In nanostructured PTO/LSMO similar to the present study, the thickness of the LSMO layer determines the location of 180 domain walls. 19 Internal bias can couple with charge ordering at the PTO/LSMO interface. 20 Here, we employ photoemission electron microscopy using soft x-rays (X-PEEM) to study the ferroelectric imprint and Mn valency at the PTO/nanostructured LSMO buried interface in a spatially resolved manner.…”
Section: Introductionmentioning
confidence: 99%